CORRELATION OF FAMILY SUPPORT AND FAMILY RESILIENCE WITH DHF PREVENTION BEHAVIOR IN OLDER ADULTS: Hubungan Dukungan dan Ketahanan Keluarga dengan Perilaku Pencegahan DBD pada Lansia - Sumarsih, Gusti; Freska, Windy; Claudia, Lara (Universitas Airlangga, 2024)
Background: The elderly are a vulnerable age group for Dengue Haemorrhagic Fever (DHF) with a high risk of death. Families must carry out their roles in efforts to prevent DHF in older adults. Purpose: This study aims to identify the correlation between family support and resilience with DHF prevention behavior. Methods: This study used a correlational design to detect a relationship between family support and resilience variables and DHF prevention behavior by older adults. The research location was at the Andalas Health Center in Padang, with 96 randomly recruited from seven elderly Integrated Public Health Centers. The instrument consisted of three closed-question questionnaires. Family support is identified through informational, reward, instrumental, and emotional indicators, while family resilience includes relationship communication, positive framing, and external resources. Data were analyzed using the Spearman Rho test. Results: Most respondents were older adults (73.96%) aged 60-65 (68.75%). The correlation test between family support and family resilience with DHF prevention behavior has a significant relationship (0.00). Testing the correlation partially on each indicator shows the highest level of correlation on the instrumental indicator (0.83). The correlation between family support and resilience was highest on emotional and communication-relationship indicators (0.71). Conclusion: Family support and resilience are correlated with DHF prevention behavior by the elderly. Emotional support from the family through communication appropriate to the older adults' age phase is needed to prevent DHF.